2022
DOI: 10.7717/peerj.14432
|View full text |Cite
|
Sign up to set email alerts
|

A pan-cancer analysis of the oncogenic role of ribonucleotide reductase subunit M2 in human tumors

Abstract: Background Recent studies have identified ribonucleotide reductase subunit M2 (RRM2) as a putative promoter of tumors. However, no systematic analysis of its carcinogenicity has been conducted. Methods The potential functions of RRM2 in various tumor types were investigated using data from the Genotype-Tissue Expression (GTEx), the Clinical Proteomic Tumor Analysis Consortium (CPTAC), the Cancer Genome Atlas (TCGA), the Human Protein Atlas … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 59 publications
1
4
0
Order By: Relevance
“…MMP12 was significantly and positively correlated with immune cell levels, and immune cell scores were higher in the MMP12 high-expression group, suggesting that MMP12 was very closely associated with immune cells. We further validated this using the TIMER algorithm ( Chen et al., 2022c ; Li et al., 2020 ; Li et al., 2022b ; Liu et al., 2022a ) and multicenter single-cell sequencing, and the results were mostly consistent with our expectations; upregulation of MMP12 expression was not only associated with increased infiltration levels of five immune cell types but was also widely present in DCs as well as monocytes/macrophages. DCs are involved in antitumor immunity by activating T cells, and macrophages can participate in immune regulation through phagocytosis, antigen presentation, and the secretion of cytokines ( Wynn & Vannella, 2016 ).…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…MMP12 was significantly and positively correlated with immune cell levels, and immune cell scores were higher in the MMP12 high-expression group, suggesting that MMP12 was very closely associated with immune cells. We further validated this using the TIMER algorithm ( Chen et al., 2022c ; Li et al., 2020 ; Li et al., 2022b ; Liu et al., 2022a ) and multicenter single-cell sequencing, and the results were mostly consistent with our expectations; upregulation of MMP12 expression was not only associated with increased infiltration levels of five immune cell types but was also widely present in DCs as well as monocytes/macrophages. DCs are involved in antitumor immunity by activating T cells, and macrophages can participate in immune regulation through phagocytosis, antigen presentation, and the secretion of cytokines ( Wynn & Vannella, 2016 ).…”
Section: Discussionsupporting
confidence: 78%
“…The Tumor Immune Estimation Resource (TIMER) ( Li et al., 2020 ; Chen et al., 2022c ; Liu et al., 2022a ; Li et al., 2022b ) is an online database that allows comprehensive detection of immune cell infiltration levels. The data for six immune-infiltrating cells were downloaded from the database.…”
Section: Methodsmentioning
confidence: 99%
“…Using the Kaplan-Meier survival curve and the log-rank test, overall survival in relation to RRM2 expression in HCC patients was examined. By calculating the receiver operating characteristic (ROC) and the area under the curves (AUCs), the diagnostic value of RRM2 was obtained using the "time ROC" and "ggplot2" R packages [7]. We used the "R-forestplot" and "R-survival" packages to analyze and illustrate the univariate and multivariate Cox regression analysis.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, RRM2 was reported to be predictive of lung adenocarcinoma prognosis. Our previous study has demonstrated that RRM2 is involved in HBVrelated hepatocellular carcinoma (HCC), whereas its precise functions and mechanisms in HCC caused by HBV still unclear [7].…”
Section: Introductionmentioning
confidence: 99%
“…This mechanism could potentially provide a plausible rationale for the upregulated RCAN3 gene among smokers with CAD. Furthermore, TRAV4 , which encodes T-cell receptor alpha variable 4, and JCHAIN , which encodes Ig J Chain, have been reported to be related to adenocarcinoma [ 38 , 39 ]. However, no previous studies have examined their connection to CAD or smoking.…”
Section: Discussionmentioning
confidence: 99%